2000
DOI: 10.1074/jbc.m001810200
|View full text |Cite
|
Sign up to set email alerts
|

Expression Cloning of an Oxysterol 7α-Hydroxylase Selective for 24-Hydroxycholesterol

Abstract: The synthesis of 7␣-hydroxylated bile acids from oxysterols requires an oxysterol 7␣-hydroxylase encoded by the Cyp7b1 locus. As expected, mice deficient in this enzyme have elevated plasma and tissue levels of 25-and 27-hydroxycholesterol; however, levels of another major oxysterol, 24-hydroxycholesterol, are not increased in these mice, suggesting the presence of another oxysterol 7␣-hydroxylase. Here, we describe the cloning and characterization of murine and human cDNAs and genes that encode a second oxyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
134
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 27 publications
2
134
1
Order By: Relevance
“…CYP39A1 represents another oxysterol 7a-hydroxylase with a strong preference for 24S-hydroxycholesterol (Li-Hawkins et al 2000a). Conversion into 24S-hydroxycholesterol is an important brain-specific mechanism for the elimination of cholesterol across the blood-brain barrier (Lü tjohann et al 1996;Bjö rkhem et al 1997Bjö rkhem et al , 1998Bjö rkhem and Eggertsen 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CYP39A1 represents another oxysterol 7a-hydroxylase with a strong preference for 24S-hydroxycholesterol (Li-Hawkins et al 2000a). Conversion into 24S-hydroxycholesterol is an important brain-specific mechanism for the elimination of cholesterol across the blood-brain barrier (Lü tjohann et al 1996;Bjö rkhem et al 1997Bjö rkhem et al , 1998Bjö rkhem and Eggertsen 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous multiple northern blot analysis showed that CYP39A1 is exclusively expressed in murine liver tissue (Li-Hawkins et al 2000a). The present block-cycler RT-PCR analysis yielded mRNA expression of the human isozyme in human liver, prostate and, as shown here for the first time, to an apparently lesser also extent in the human CNS (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP39A1 encodes an oxysterol 7α-hydroxylase enzyme that appears to have a preference for 24S-hydroxycholesterol as a substrate [53]. It was originally cloned form the liver, although low levels have been detected in the eye [54,55] and brain [56].…”
Section: Cyp39a1mentioning
confidence: 99%
“…It was originally cloned form the liver, although low levels have been detected in the eye [54,55] and brain [56]. A notable feature is the sexually dimorphic, with females expressing a higher level of both the mRNA and the protein [53].…”
Section: Cyp39a1mentioning
confidence: 99%